A review of the genus Eugaster Serville, 1838 (Orthoptera, Tettigoniidae, Hetrodinae): a multifaceted approach - Cassar, Louis-F; Massa, Bruno; Gauci, Adam; Bartolo, Angela G; Schembri, Sarah (Zootaxa, 2024)
Overall coloration, size and thoracic morphology have formed the basis for taxonomic differentiation of taxa within the genus Eugaster at specific or subspecific levels over the years. The present study employs a range of methods to examine the morphology of 58 specimens (18♂♂ and 40♀♀) from Morocco, Algeria and Tunisia, collected from altitudes varying between 10 and 1795 metres AMSL. Moroccan sampling sites include localities on both the north and south of the High Atlas and from either side of the Middle Atlas, i.e., the Anti-Atlas, Western Meseta and High Plateau. The various techniques involve the characterisation of the five key colour forms and an investigation to examine links between colour form and geographical location and altitude, biometric analysis comprising selected variables, thoracic structure examination through feature extraction and edge detection, microscopy to examine male stridulatory files, an examination of the male genital sclerite structure for the presence of titillators, as well as molecular and phylogenetic analysis. Statistical tests are performed for results pertaining to biometrics, thoracic skeletisation, and the number of pegs on stridulatory organs. From results obtained, this study finds no basis to support the notion of the various taxa described in the past being assigned the rank of species and considers these to be infraspecific variants or forms. Consequently, the present authors propose to synonymise Eugaster guyoni (Serville, 1838) with Eugaster spinulosa (Johannson, 1763), resulting in the genus Eugaster being represented in North Africa by a unique but highly variable taxon, in terms of coloration, size and thoracic morphology.